Analisis Penetapan Pengangkatan Anak (Tabanni) di Pengadilan Agama Surabaya Dalam Perspektif Kompilasi Hukum Islam dan Peraturan Perundang-Undangan Nomor 54 Tahun 2007 - Masfufah, Siti Himmatul; Murniati, Dewi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The existence of this determination analysis is because the author wants to know how the panel of judges decides the case of determining the adoption of a child (tabanni) at the Surabaya Religious Court. In this case, the author uses a qualitative research method to find out the analysis of the judge's decision at the Surabaya Religious Court regarding the case of determining the adoption of a child (tabanni) by conducting observations and viewing several decisions on the Surabaya Religious Court website. From here, the author then conducted an analysis, after conducting research, the author concluded that tabanni and adoption both have the meaning of adopting a child, but the difference is that adoption is adopting a child and considering the child as a legitimate child (biological child) if tabanni is adopting a child but does not consider the child as a legitimate child (biological child)